The Effect of Village Fund Allocation Policy on Development - Nasution, Syamsul Hidayat; Siregar, Nina Siti Salmaniah; Jamaludin, Yanhar (Borong Newinera Publisher, 2025)
This study aims to analyze the implementation of Mandailing Natal Regent Regulation Number 11 of 2024 concerning Village Fund Allocation in increasing development in Singengu Julu Village, Kotanopan District, Mandailing Natal Regency. Through a descriptive qualitative approach, this study collects data through interviews, observations, and documentation studies. The results of the study show that the allocation of village funds in Singengu Julu Village focuses on infrastructure development, with most of the funds used for the construction of village roads, irrigation canals, and village hall renovations. Community empowerment programs are also being implemented, although the participation of marginalized groups, such as women and the elderly, is still limited. In addition, supervision and transparency in the use of village funds have been implemented, but it needs to be improved so that more people can access and understand this information. Although the positive impact on local infrastructure and economy is already being felt, the challenges faced include the low capacity of human resources at the village level and the lack of involvement of all elements of society in planning. This study recommends increasing community participation, strengthening the capacity of village apparatus, and increasing transparency and accountability in village fund management to achieve more inclusive and sustainable development.